ANALYSIS OF PROJECT DELAYS FROM A HUMAN RESOURCE MANAGEMENT PERSPECTIVE USING FAULT TREE ANALYSIS (FTA) IN A HOSPITAL CONSTRUCTION PROJECT - Safira Farras Pramesti; Muhammad Isradi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Project delays remain a critical issue in construction projects, particularly in hospital developments that involve high complexity, strict functional requirements, and intensive coordination among multidisciplinary teams. Empirical evidence indicates that many delays are not solely caused by technical or material factors, but are strongly associated with deficiencies in human resource management (HRM). This study addresses the question of how human resource–related factors structurally contribute to project delays and what root causes dominate these delays in hospital construction projects. To answer this question, the research applies Fault Tree Analysis (FTA) as the primary analytical method, using a deductive and top–down approach to decompose the main delay event into intermediate and basic events related to HRM practices. A case study was conducted on a hospital construction project in Jakarta that experienced significant schedule deviation. Data were collected through questionnaires, interviews with project personnel, and project documentation, and subsequently modeled into a fault tree structure using logical AND and OR relationships. The results indicate that ineffective workforce planning and weak coordination and communication systems constitute the most critical root causes of project delays. These factors trigger cascading effects such as work interruptions, rework, low labor productivity, and delayed decision-making, which collectively lead to schedule overruns. This study contributes academically by demonstrating the applicability of FTA as a structured root-cause analysis tool for project delays from a human resource management perspective, thereby extending delay analysis literature beyond conventional technical and descriptive approaches, particularly in the context of hospital construction projects.